2008
DOI: 10.1002/ijc.23756
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral rhIL‐12 administration in head and neck squamous cell carcinoma patients induces B cell activation

Abstract: The objectives of this study were to investigate the effects of intratumorally (i.t.) administered recombinant human interleukin-12 (rhIL-12) on the distribution and function of B cells in the primary tumors, the locoregional lymph nodes and peripheral blood of head and neck squamous cell carcinoma (HNSCC) patients. The initial characterization of the patients participating in the phase Ib and phase II studies has previously been reported. After rhIL-12 treatment, fewer secondary follicles with a broader outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 36 publications
(41 reference statements)
2
49
0
Order By: Relevance
“…Invest New Drugs (2019) 37: [1][2][3][4][5][6][7][8]The survival time difference between the control and treatment groups was however statistically significant (P = 0.0028).…”
Section: The Role Of the Host In Tigilanol Tiglate Efficacymentioning
confidence: 99%
“…Invest New Drugs (2019) 37: [1][2][3][4][5][6][7][8]The survival time difference between the control and treatment groups was however statistically significant (P = 0.0028).…”
Section: The Role Of the Host In Tigilanol Tiglate Efficacymentioning
confidence: 99%
“…After i.t. rhIL-12 treatment of HNSCC patients, significant effects were noted on B cells, with altered lymph node architecture in every IL-12-treated patient and excessive peritumoral infiltration of B cells in some patients (87,88).…”
Section: Clinical Trials: Toxicity Tempers the Potential Of Il-12 As mentioning
confidence: 99%
“…When administered intratumorally into Head and Neck Squamous cell carcinoma (HNSCC) patients, Van Herpen et al observed it increases the level of B cells within the tumor, stimulates B cell proliferation, increases B cell expression of IFN -ᵧ and skews the plasma antibody profile towards the Th 1 phenotype (Van Herpen et al, 2008). It regulates cellular immunity by the production and activation of cytolytic T cells and NK cells and also induces the production of cytokines.…”
Section: Cell Mediated Immunotherapymentioning
confidence: 99%